(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The objective of this paper is to present the approximation between law and politics, highlighting the themes of judicialization and judicial activism. We present a differentiation and eventual meeting points between the concepts throught some authors view, such as Trindade and Oliveira (2012), Veríssimo (2013), Tassinari and Oliveira (2014), Nunes Junior (2016) and Nobre and Rodriguez (2011). This study aims to point out possible changes in the current normative paradigm (NOBRE; RODRIGUEZ, 2011) so that non-traditional alternatives and solutions (which means, not based on a normative perspective) can flourish and indicate new institutional and grammatical designs of law. It is inferred that the authors believe that judicialization of politics and judicial activism are concepts permeated by a normative and engendering view of social conflicts and ways to solve them. Thinking them in-depth means giving up institutional models and traditional normative theories that have not been worked and open space for alternatives that consider the specificities of the State and national institutions to be taken into account in conflict resolution.